Role of Serum Lactate Dehydrogenase in Isolated Head Injury - Mohit Bhardwaj; Bhavinder Arora (Indian Journal of Neurosurgery)
In recent years, some encouraging reports have appeared on assessing the degree of brain damage by estimating serum and cerebrospinal fluid enzymes such as lactate dehydrogenase (LDH). In our study, we included 100 patients with isolated head injury arriving at trauma center, PGIMS Rohtak within 24 hours of injury, studied levels of serum LDH on days 1, 3, and 7 of injury, and concluded that levels have diagnostic as well as prognostic significance.